Blockchain and NFTs: Transforming Traditional Value Chains in the Global Creative Economy (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study examines how blockchain technology and non-fungible tokens (NFTs) are transforming traditional value chains in the global creative economy. The research employs a qualitative case study approach, analyzing prominent NFT platforms and creative industry applications across music, digital art, and gaming sectors. Through semi-structured interviews with 25 creative entrepreneurs and platform developers, combined with secondary data analysis of blockchain transactions, this study identifies key disruptions in creative value creation, distribution, and monetization models. Findings reveal that blockchain-enabled disintermediation reduces traditional gatekeepers' control, while smart contracts facilitate automated royalty distribution and direct artist-to-consumer relationships. However, significant challenges persist, including environmental sustainability concerns, regulatory uncertainty, and market volatility. This research contributes to understanding how decentralized technologies reshape creative industry value networks and provides strategic implications for creative entrepreneurs navigating digital transformation.
Keywords: blockchain technology; non-fungible tokens; creative economy; value chain transformation; digital disruption